Low doses of ionizing radiation and circulatory diseases: a systematic review of the published epidemiological evidence. - McGale, P; Darby, S (2005)
Recent analyses of mortality among atomic bomb survivors have suggested a linear dose-response relationship between ionizing radiation and diseases of the circulatory system for exposures in the range 0-4 Sv. If confirmed, this has substantial implications. We have therefore reviewed the published literature to see if other epidemiological data support this finding. Other studies allowing a comparison of the rates of circulatory disease in individuals drawn from the same population but exposed to ionizing radiation at different levels within the range 0-5 Gy or 0-5 Sv were identified through systematic literature searches. Twenty-six studies were identified. In some, disease rates among those exposed at different levels may have differed for reasons unrelated to radiation exposure, while many had low power to detect effects of the relevant magnitude. Among the remainder, one study found appreciable evidence that exposure to low-dose radiation was associated with circulatory diseases, but five others, all with appreciable power, did not. We conclude that the other epidemiological data do not at present provide clear evidence of a risk of circulatory diseases at doses of ionizing radiation in the range 0-4 Sv, as suggested by the atomic bomb survivors. Further evidence is needed to characterize the possible risk.